Comparison of Videolaryngoscopy and Direct Laryngoscopy for Tracheal Intubation in Obstetrics: A Mixed-methods Systematic Review and Meta-Analysis. Issue 1 (23rd March 2022) - Howle, R.; Onwochei, D.; Harrison, S.L.; Desai, N.
Abstract : ( Can J Anaesth . 2021;68:546–565. doi: 10.1007/s12630-020-01908-w. Epub January 12, 2021) While intubation is sometimes necessary, it can be especially challenging in obstetric patients. Difficult and failed intubation increases the risk of maternal and fetal adverse outcomes. To help mitigate this, videolaryngoscopy has become the standard of care because, compared with direct laryngoscopy, videolaryngoscopy has shown to decrease the occurrence of intubation failures and complications. The aim of this study is to perform a mixed-methods systematic review and meta-analysis to compare the efficiency, efficacy, and safety of videolaryngoscopy and direct laryngoscopy specifically in regards to parturients.